On cultural heritage metadata. (1st January 2012) - Papatheodorou, Christos
The management of cultural heritage metadata is a multifaceted process depending on the diversity and heterogeneity of the cultural objects, the structure of their collections and the information needs of the communities that generate, access and study them. This paper reports the results derived from the special track on metadata and semantics for cultural collections and applications, which was a part of the 5th International Conference on Metadata and Semantic Research (MTSR 2011), held in Yasar University, Izmir, Turkey, 12–14 October 2011.